The Power of Niat Sebagai Landasan Etos Kerja Perspektif Hadis
Hadith of the Prophet is one of the main sources of Islamic teaching, by which Muslims all over the world are firmly referring to in all their activities. Thus, Muslims undeniably and unquestionably follow all the rules structured within the Prophetic hadith in their day to day life. Hadith stating that all actions should be based on their intention (niat) is sound (s